Mandatory for Armenia - (:unkn) unknown (My University)
In 1920, a "Mandatory for Armenia" (or American Mandate) was proposed under the League of Nations to provide protection, economic aid, and administrative oversight to the newly independent First Republic of Armenia. Although President Woodrow Wilson strongly supported it, the U.S. Senate rejected the mandate in June 1920, leading to the failure of the Treaty of Sèvres and the subsequent sovietization of Armenia
United States. Congress. House. Committee on Foreign Affairs.- Moores, Merrill ; Flood, Henry Delaware.- [Washington, Govt. print. off., 1920] - 7, 4 p. 23 cm.
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ԱՄՆ-ի Կոնգրեսի գրադարանից
https://www.loc.gov/item/20026619/
Keywords: Armenia-Foreign relations-United States; United States Foreign relations Armenia